Heat-induced triploids in Brycon amazonicus: A strategic fish species for aquaculture and conservation - Do Nascimento, Nivaldo Ferreira; Bertolini, Rafaela Manchin [UNESP]; Lopez, Lucia Soares [UNESP]; Nakaghi, Laura Satiko Okada; Monzani, Paulo Sérgio; Senhorini, José Augusto [UNESP]; Vianna, Roberto Castro; Yasui, George Shigueki [UNESP] (Cambridge University Press (CUP), 2021)
Summary Triploidization plays an important role in aquaculture and surrogate technologies. In this study, we induced triploidy in the matrinxã fish (Brycon amazonicus) using a heat-shock technique. Embryos at 2 min post fertilization (mpf) were heat shocked at 38°C, 40°C, or 42°C for 2 min. Untreated, intact embryos were used as a control. Survival rates during early development were monitored and ploidy status was confirmed using flow cytometry and nuclear diameter analysis of erythrocytes. The hatching rate reduced with heat-shock treatment, and heat-shock treatments at 42°C resulted in no hatching events. Optimal results were obtained at 40°C with 95% of larvae exhibiting triploidy. Therefore, we report that heat-shock treatments of embryos (2 mpf) at 40°C for 2 min is an effective way to induce triploid individuals in B. amazonicus.
Keywords: Aquaculture; Chromosome manipulation; Fish; Heat shock; Polyploidy